The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.epsl.2016.11.017
|View full text |Cite|
|
Sign up to set email alerts
|

Short-lived increase in erosion during the African Humid Period: Evidence from the northern Kenya Rift

Abstract: The African Humid Period (AHP) between ∼15 and 5.5 cal. kyr BP caused major environmental change in East Africa, including filling of the Suguta Valley in the northern Kenya Rift with an extensive (∼2150 km 2 ), deep (∼300 m) lake. Interfingering fluvio-lacustrine deposits of the Baragoi paleo-delta provide insights into the lake-level history and how erosion rates changed during this time, as revealed by delta-volume estimates and the concentration of cosmogenic 10 Be in fluvial sand. Erosion rates derived fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 44 publications
(81 reference statements)
2
24
0
Order By: Relevance
“…Similarly, as relatively unweathered rock that contains longer cracks (joints) or denser flaws (foliation or bedding) is exhumed, weathering rates might initially be large but then slow down as the rock adjusts—through subcritical cracking along these inherent weaknesses—to its new stress‐loading conditions. We hypothesize that such a relationship might provide a mechanistic explanation for observations of faster regolith production rates in faster eroding landscapes [ Heimsath et al ., 2012], or initially fast, followed by slower, erosion after a climate change [ Garcin et al ., ].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, as relatively unweathered rock that contains longer cracks (joints) or denser flaws (foliation or bedding) is exhumed, weathering rates might initially be large but then slow down as the rock adjusts—through subcritical cracking along these inherent weaknesses—to its new stress‐loading conditions. We hypothesize that such a relationship might provide a mechanistic explanation for observations of faster regolith production rates in faster eroding landscapes [ Heimsath et al ., 2012], or initially fast, followed by slower, erosion after a climate change [ Garcin et al ., ].…”
Section: Discussionmentioning
confidence: 93%
“…Physical experiments provide an alternative approach to studying the dynamics of the transfer zone, including terrace formation (Baynes et al, 2018;Frankel et al, 2007;Gardner, 1983;Lewis, 1944;Mizutani, 1998;Schumm and Parker, 1973;Wohl and Ikeda, 1997) and the evolution of Q s,out (Bonnet and Crave, 2003;van den Berg van Saparoea and Postma 2008). Most experimental studies have tested the cutting of terraces due to base-level fall (BLF; Frankel et al, 2007;Gardner, 1983;Schumm and Parker, 1973) or explained their cutting through autogenic processes (Lewis, 1944;Mizutani, 1998). Only one experimental study by Baynes et al (2018) investigated terrace formation as a response to changes in Q s,in or Q w , but this study focused on vertical incision into bedrock and strath-terrace cutting.…”
Section: Introductionmentioning
confidence: 99%
“…(2) Strong positive response: observed in regional studies that have shown an increase in long-term erosion rates with precipitation and runoff, sometimes mediated by relief under high uplift rates (e.g., Bookhagen & Strecker, 2012;Garcin et al, 2017;Henck et al, 2011). (3) Strong but complex response: Watershed studies of sediment yield over decadal time scales (Jeffery et al, 2014;Langbein & Schumm, 1958;Wilson, 1973) and evidence from recent millennial-scale hillslope erosion rate estimates (Schaller et al, 2018;Torres Acosta et al, 2015) have shown a hump-shaped response of erosion to an increase in precipitation, sometimes with multiple peaks (Walling & Webb, 1983). In this humped response, a positive dependence was largely limited to arid and semiarid climates; but a further increase in precipitation led to a downturn in sediment yield and to lower erosion rates.…”
Section: Introductionmentioning
confidence: 99%